AN APPLICATION OF THE DISCOVERY LEARNING THROUGH PUZZLE GAMES TO IMPROVE GEOGRAPHY LEARNING ACTIVITIES AND OUTCOMES AT SMAN 2 SELAYAR - Astuti, Alfiani Dwi; Maddatuang, Maddatuang; Adna, Andi Nur (USN Kolaka, 2024)
Abstract This research aims to improve the activities and learning outcomes of student from class X 2 SMAN 2 Selayar. This research uses the Discovery Learning Model through Puzzle Games, with each cycle consisting of planning stages, implementing actions, observing and reflecting. The subjects of this research were students in class X 2 of SMA Negeri 2 Selayar for the 2023/2024 academic year. Data sources were obtained from teachers and students. The data collection is carried out through in-depth interviews, observations, summative assessments, and documentation that will be analyzed descriptive qualitatively and quantitatively. Based on the research results, it can be concluded that the application of learning using the Discovery Learning through puzzle games can improve the learning outcomes and activities students of class X 2 at SMA Negeri 2 Selayar. On first cycle , the percentage of achievement of student learning activities was 71.875% then increased in second cycle to 93.23%. The increase in learning outcomes can be seen from the knowledge aspect in the pre-cycle reaching 37.5% completeness, in the first cycle reaching 56.25% completeness and increasing in the second cycle with 93.75% completeness.